Structure, compression and thermally insulating properties of cellulose diacetate-based aerogels - Sizhao Zhang; Xing Huang; Junzong Feng; Fangwei Qi; Dianyu E; Yonggang Jiang; Liangjun Li; Shixian Xiong; Jian Feng (Materials & Design, 2020)
We report on the relationship for structure, compression and thermal insulation properties of cellulose diacetate-based aerogels (CDBAs), prepared from cellulose diacetate (CDA) cross-linked with 2, 4-toluene diisocyanate (TDI) by using sol-gel and supercritical drying processes. Lower reactant dosage (no matter CDA or TDI), can induce smaller shrinkage (~12%) after supercritical drying, and even to achieve lower density (~0.06 g/cm3) of CDBAs. Monolith CDBAs have typical three-dimensional networks with lamella reinforced fiber-like skeletons and nanometric pores. Such reinforced networking structure with lamellas as reinforcement is responsible for the maximum compression strength of ~1.29 MPa at 10% strain and compressive modulus of 21.86 MPa in CDBAs. Besides, the excessive addition of TDI leads to accelerate the growth of secondary fiber-like skeletons to ultimately divide the large pores into the small ones inside the formed network. This structural evolution enables to synergistically reduce gaseous thermal conductivity by means of Knudsen effect and increase that of solid part due to wider solid contacted area. The minimum total thermal conductivity of ~0.0313 W m−1 K−1 at ambient environment is obtained when the synergetic effects reach up to the critical balance, whose solid and gaseous proportions are calculated as 51.76 and 48.24%, respectively. Keywords: Cellulose diacetate, Aerogel, Structure, Compression, Thermal insulation